Characterization and application of orange peel as an adsorbent for cationic dye removal from aqueous solution - Haas, Aline; Santos, Eliane Pereira dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
With the great generation of colored effluents, several methods for the removal of the color are used, being one of them the method of adsorption in solid medium. In this paper, the in natura orange peel was used as the alternative biomass for the adsorption process of methylene blue, which was characterized by moisture content, pH, apparent density, iodine number, and methylene blue index. To determine the adsorptive capacity of the methylene blue dye, pH 7 was obtained as favorable, the adsorption process showed an adsorption of 82% of the methylene blue dye and a 10 min equilibrium time, where the Freundlich isotherm presented a better adaptation to the adsorption process in orange peel, with its maximum adsorption capacity of 3.9630 mg g-1, for the methylene blue dye.